La generación de opinión pública ¿Asunto público o privado? (2004)
This papers presents a series of approximations and approaches to the subject of PUBLIC OPINION not only as a phenomenon typical of public affairs, but rather, furthermore, from within its PRIVATE approach and Cosmovision.In effect, and despite the fact that the paradigm of PUBLIC OPINION is identified with postulates of manifested, visible, accessible, and collective interest, that is, from its PUBLIC dimension, this paper aims at demonstrating that it is the contrary dimension (the PRIVATE) that, ever since then till today, has made an appropriation of the PUBLIC OPINION making us believe that the street protests, the expositions expressed by the so called Opinion Leaders, and the opinion polis made public through mass media are the people’s own manifestations and which reflect the public thoughts over the issues affecting a majority.Inclusively, and without being whatsoever boastful, our intention is highlighted within the premise that a vindication of that which is PUBLIC is urgent and immediate as an alternative to save the true dimension of PUBLIC OPINION, and thus affronting the series of problems the country is living, especially those related to the collective ideals, among which is the ever-evasive PEACE